2022
DOI: 10.3389/fimmu.2022.963445
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cells as treatment for acute respiratory distress syndrome. Case Reports following hematopoietic cell transplantation and a review

Abstract: Acute respiratory distress syndrome (ARDS) is a life-threatening lung disease. It may occur during the pancytopenia phase following allogeneic hematopoietic cell transplantation (HCT). ARDS is rare following HCT. Mesenchymal stromal cells (MSCs) have strong anti-inflammatory effect and first home to the lung following intravenous infusion. MSCs are safe to infuse and have almost no side effects. During the Covid-19 pandemic many patients died from ARDS. Subsequently MSCs were evaluated as a therapy for Covid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 177 publications
0
6
0
Order By: Relevance
“…In 2020, Chinese physicians successively shared several cases of severe pneumonia treated with MSCs ( 82 88 ), and then similar cases began to be reported in other countries and regions ( 87 96 ). The dose range for an intravenous drip of MSCs was ( 1 – 3 ) × 10 6 kg in most of the cases ( 82 90 , 96 ). It is also important to note that none of these cases had a history of cancer, except for three cases reported in Sweden in 2022 ( 96 ) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In 2020, Chinese physicians successively shared several cases of severe pneumonia treated with MSCs ( 82 88 ), and then similar cases began to be reported in other countries and regions ( 87 96 ). The dose range for an intravenous drip of MSCs was ( 1 – 3 ) × 10 6 kg in most of the cases ( 82 90 , 96 ). It is also important to note that none of these cases had a history of cancer, except for three cases reported in Sweden in 2022 ( 96 ) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 91%
“…The dose range for an intravenous drip of MSCs was ( 1 – 3 ) × 10 6 kg in most of the cases ( 82 90 , 96 ). It is also important to note that none of these cases had a history of cancer, except for three cases reported in Sweden in 2022 ( 96 ) ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three cases of ARDS, a rare side effect of HCT, have been treated with MSCs. Two patients given BM-MSCs did not survive, although the third patient who received DSCs, showed a dramatic response, and has survived seven years post-treatment thus far ( 176 ). DSC therapy was also recently shown to be safe and capable of improving oxygenation, decreasing inflammatory cytokine levels, and clearing pulmonary infiltrates in patients with COVID‐19 ( 172 ).…”
Section: Cell Therapy For Gvhdmentioning
confidence: 99%
“…16 MSCs are not brandnew therapy in the treatments of pulmonary diseases. Previous studies have demonstrated that patients with chronic obstructive pulmonary disease, 16 ARDS 17 or pulmonary fibrosis 18,19 could benefit from MSCbased therapy which reduces the inflammation and pulmonary tissue damage, improves the respiratory function, pulmonary microenvironment and reduces the mortality. At the same time, the anti-infammatory and immunomodulatory characteristics of MSC-based therapy make them as ideal candidates for the treatment of patients with acute and chronic inflammatory lung diseases.…”
Section: Introductionmentioning
confidence: 99%